Abnormal Ca2+ handling contributes to the impairment of aortic smooth muscle contractility in Zucker diabetic fatty rats. (April 2020) - Yang, Hui; Chen, Xiao-Yan; Kuang, Su-Juan; Zhou, Meng-Yuan; Zhang, Li; Zeng, Zheng; Liu, Lin; Wu, Fei-Long; Zhang, Meng-Zhen; Mai, Li-Ping; Yang, Min; Xue, Yu-Mei; et al.
Abstract: Vascular dysfunction is a common pathological basis for complications in individuals affected by diabetes. Previous studies have established that endothelial dysfunction is the primary contributor to vascular complications in type 2 diabetes (T2DM). However, the role of vascular smooth muscle cells (VSMCs) in vascular complications associated with T2DM is still not completely understood. The aim of this study is to explore the potential mechanisms associated with Ca 2+ handling dysfunction and how this dysfunction contributes to diabetic vascular smooth muscle impairment. The results indicated that endothelium-dependent vasodilation was impaired in diabetic aortae, but endothelium-independent vasodilation was not altered. Various vasoconstrictors such as phenylephrine, U46619 and 5-HT could induce vasoconstriction in a concentration-dependent manner, such that the dose-response curve was parallel shifted to the right in diabetic aortae, compared to the control. Vasoconstrictions mediated by L-type calcium (Cav1.2) channels were attenuated in diabetic aortae, but effects mediated by store-operated calcium (SOC) channels were enhanced. Intracellular Ca 2+ concentration ([Ca 2+ ]i ) in VSMCs was detected by Fluo-4 calcium fluorescent probes, and demonstrated that SOC-mediated Ca 2+ entry was increased in diabetic VSMCs. VSMC-specific knockout of STIM1 genes decreased SOC-mediated and phenylephrine-induced vasoconstrictive response in mice aortae. Additionally, Orai1 expression was up-regulated, Cav1.2 expression was downregulated, and the phenotypic transformation of diabetic VSMCs was determined in diabetic aortae. The overexpression of Orai1 markedly promoted the OPN expression of VSMCs, whereas SKF96365 (SOC channel blocker) reversed the phenotypic transformation of diabetic VSMCs. Our results demonstrated that the vasoconstriction response of aortic smooth muscle was weakened in type 2 diabetic rats, which was related to the downregulation of the Cav1.2 channel and the up-regulation of the SOC channel signaling pathway. Highlights: Vasoconstriction of aorta attenuate in type 2 diabetic rats. Decreased Cav1.2 and increased SOC channels in aortas from diabetic rats. Phenotype transformation of VSMCs occurs in the hyperglycemia.